Conductive film from silver nanowires prepared with polyol method - Anh, Đỗ Phương; Tuyết, Nguyễn Thị Ánh; Thông, Nguyễn Văn; Thịnh, Nguyễn Văn; Ơn, Đỗ Viết; Tùng, Võ Thanh; Chương, Trương Văn (Hue University Journal of Science: Natural Science, 2021)
In this paper, silver nanowires were prepared with the polyol method under ultrasonication. The optimal concentration of polyvinyl pyrrolidone in the reaction mixture was also determined. These nanowires were characterized with the XRD, SEM, and UV-Vis techniques. The conductive solution possesses a low resistance, good adhesion, high flexibility, and thermal stability. The solution was utilized to fabricate a conductive film, which might open up new technology applications.